Space-time analysis of the first year of COVID-19 pandemic in the city of Rio de Janeiro, Brazil - Cleber Vinicius Brito dos Santos; João Roberto Cavalcante; Paula Cristina Pungartnik; Raphael Mendonça Guimarães (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2021)
ABSTRACT: Objective: To describe the space-time evolution of cases and deaths due to COVID-19 in the Rio de Janeiro municipality, Brazil, during the first year of the pandemic. Methods: An ecological study was carried out. The units of analysis were the neighborhoods of the city of Rio de Janeiro. Incidence and mortality rates, excess risk, Global Moran's Index (Moran's I), local indicator for spatial association, standardized incidence ratio, and standardized mortality ratio were estimated for neighborhoods in the municipality of Rio de Janeiro. Results: Over the first year of the pandemic, registries in the city of Rio de Janeiro included 204,888 cases and 19,017 deaths due to COVID-19. During the first three months of the pandemic, higher incidence rates were verified in the municipality compared with the state of Rio de Janeiro and Brazil, in addition to higher mortality rates compared with the state of Rio de Janeiro and Brazil from May 2020 to February 2021. Bonsucesso was the neighborhood with the highest incidence and mortality rates, and throughout the neighborhoods and months, there is no synchrony between the worst moments of the COVID-19 pandemic. Conclusion: The authors emphasize the need for implementing more rigid control and prevention measures, increasing case detection, and accelerating the COVID-19 immunization campaign.